PENGELOLAAN PENYIMPANAN BAHAN PANGAN PERISHABLE; DAGING, IKAN, AYAM DI HOT KITCHEN RESTORAN GORMETERIA BANDUNG: - Heri Atmojo; Ilham Robbani (JURNAL PARIWISATA VOKASI, 2025)
ABSTRACT This study aims to determine and analyze the storage of perishable foodstuffs (meat, fish, and chicken) stored in freezer boxes and chiller cabinets in relation to temperature, containers, shelf placement, and cleanliness of the surrounding area, and their impact on the deterioration of perishable foodstuffs in the hot kitchen of Gormeteria Restaurant in Bandung. This study used a descriptive method, data collection techniques through observation, interviews, questionnaires, and literature studies. For measurement, the Guttman scale was used, and data presentation used a pie chart model. Data analysis techniques were taken from statistical data used to describe, simplify, and present sample data more easily. The conclusions and recommendations from the analysis of 27 kitchen staff respondents are as follows: 1. Regarding the storage temperature of perishable food ingredients at the Gormeteria Restaurant in Bandung, 63% of staff lack understanding about the management of perishable food storage in freezer boxes and chiller cabinets in relation to temperature and the condition of equipment that is poorly maintained and damaged. In the future, training on the management of perishable food storage in freezer boxes and chiller cabinets in relation to temperature and the condition of equipment that is poorly maintained and damaged at the Gormeteria Bandung restaurant, 63% of staff lack understanding about the management of perishable food storage in freezer boxes and chiller cabinets in relation to temperature and equipment conditions, which are poorly maintained and damaged. In the future, training, routine supervision, and replacement of damaged equipment are needed to achieve maximum economic value. 2. Regarding storage containers for perishable food ingredients in freezer boxes and chiller cabinets in the restaurant's hot kitchen, 67% of staff are still undisciplined and do not understand the function of these containers. In the future, there needs to be constant monitoring by supervisors and damaged containers need to be immediately replaced with new ones. 3. Regarding the placement of perishable food storage shelves in freezer boxes and chiller cabinets, 52% of staff are still not disciplined in arranging perishable food on shelves according to type and storage duration, whether it is in the chilling or freezing category. In the future, routine checks by immediate supervisors are needed to prevent greater losses. 4. Regarding the cleanliness of the food storage area, 48% of kitchen staff are still not disciplined, as it is still dirty and unhygienic, which can cause contamination and the appearance of insects/pests. In the future, training related to this is needed, and there must always be direct supervision from their superiors on a routine and periodic basis.Keywords: perishable; meat, fish, chicken, temperature, containers, storage racks, and cleanliness